2015
DOI: 10.1371/journal.pone.0134208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Adverse Drug Events from Free Text Electronic Patient Records and Information in a Large Mental Health Case Register

Abstract: ObjectivesElectronic healthcare records (EHRs) are a rich source of information, with huge potential for secondary research use. The aim of this study was to develop an application to identify instances of Adverse Drug Events (ADEs) from free text psychiatric EHRs.MethodsWe used the GATE Natural Language Processing (NLP) software to mine instances of ADEs from free text content within the Clinical Record Interactive Search (CRIS) system, a de-identified psychiatric case register developed at the South London a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…We and others have used the EHR in pharmacoepidemiology studies to identify novel adverse effects of psychotropic medications. [Blumenthal and others 2014] [Castro and others 2013; Castro and others 2012; Castro and others 2016a; Castro and others 2016b; Clements and others 2014; Gallagher and others 2012; Iqbal and others 2015; Tatonetti and others 2011]. To date, however, few studies have capitalized on the availability of psychotropic drug response data in the EHR for genetic research.…”
Section: Future Directions and Opportunitiesmentioning
confidence: 99%
“…We and others have used the EHR in pharmacoepidemiology studies to identify novel adverse effects of psychotropic medications. [Blumenthal and others 2014] [Castro and others 2013; Castro and others 2012; Castro and others 2016a; Castro and others 2016b; Clements and others 2014; Gallagher and others 2012; Iqbal and others 2015; Tatonetti and others 2011]. To date, however, few studies have capitalized on the availability of psychotropic drug response data in the EHR for genetic research.…”
Section: Future Directions and Opportunitiesmentioning
confidence: 99%
“…The ADR spans we output can serve as an input for ADR normalization, giving medical experts a consolidated summary of the reported adverse events. Iqbal et al (2015) share our motivation to identify ADR mentions in the context of electronic health records (medical correspondence, discharge letters, etc. ), which are more formal, as opposed to our focus on social media domain.…”
Section: Related Workmentioning
confidence: 99%
“…SLaM serves over 1.2 million patients and stores much of its clinical records and prescribing information in unstructured free text format. The ADR and drug episode information were extracted using an in-house developed natural language processing tools in conjunction with manual annotation [2] In this preliminary study, we focus on three types of adverse events identified in the CRIS registry: dry mouth (#event 58,347), constipation (#event 86,602) and enuresis (#93,366), which involves 20,795 distinct patients with mental health disorders. For each identified AE, we pick up the patient's past 30 days medication episodes.…”
Section: Data Source and Preparationmentioning
confidence: 99%